HRH RA JA MUDA OF PERLIS INVITES USM TO SET UP USM@PERLIS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PULAU PINANG, 11 August 2016 His Royal Highness Tuanku Syed Faizuddin Putra Ibni Tuanku Syed Sirajuddin Jamalullail, the Raja Muda of Perlis has extended an invitation to Universiti Sains Malaysia (USM) to offer study programmes and share its expertise in Perlis to benefit the people there.